Baby steps towards linking calcaneal trabecular bone ontogeny and the development of bipedal human gait. Issue 3 (14th November 2019) - Saers, Jaap P. P.; Ryan, Timothy M.; Stock, Jay T.
Abstract: Trabecular bone structure in adulthood is a product of a process of modelling during ontogeny and remodelling throughout life. Insight into ontogeny is essential to understand the functional significance of trabecular bone structural variation observed in adults. The complex shape and loading of the human calcaneus provides a natural experiment to test the relationship between trabecular morphology and locomotor development. We investigated the relationship between calcaneal trabecular bone structure and predicted changes in loading related to development of gait and body size in growing children. We sampled three main trabecular regions of the calcanei using micro‐computed tomography scans of 35 individuals aged between neonate to adult from the Norris Farms #36 site (1300 AD, USA) and from Cambridge (1200–1500 AD, UK). Trabecular properties were calculated in volumes of interest placed beneath the calcaneocuboid joint, plantar ligaments, and posterior talar facet. At birth, thin trabecular struts are arranged in a dense and relatively isotropic structure. Bone volume fraction strongly decreases in the first year of life, whereas anisotropy and mean trabecular thickness increase. Dorsal compressive trabecular bands appear around the onset of bipedal walking, although plantar tensile bands develop prior to predicted propulsive toe‐off. Bone volume fraction and anisotropy increase until the age of 8, when gait has largely matured. Connectivity density gradually reduces, whereas trabeculae gradually thicken from birth until adulthood. This study demonstrates that three different regions of the calcaneus develop into distinct adult morphologies through varying developmental trajectories. These results are similar to previous reports of ontogeny in human long bones and are suggestive of a relationship between the mechanical environment and trabecular bone architecture in the human calcaneus during growth. However, controlled experiments combined with more detailed biomechanical models of gait maturation are necessary to establish skeletal markers linking growth to loading. This has the potential to be a novel source of information for understanding loading levels, activity patterns, and perhaps life history in the fossil record. Abstract : We investigated the relationship between calcaneal trabecular bone structure and predicted changes in loading related to development of gait and body size in growing children. We show that three different regions of the calcaneus develop into distinct adult morphologies through varying developmental trajectories. These results suggest a relationship between the mechanical environment and trabecular bone architecture in the human calcaneus during ontogeny.